Phase II Study of Panitumumab in RAS Wild‐Type Metastatic Adenocarcinoma of Small Bowel or Ampulla of Vater. (19th December 2017) - Gulhati, Pat; Raghav, Kanwal; Shroff, Rachna; Varadhachary, Gauri; Javle, Milind; Qiao, Wei; Wang, Huamin; Morris, Jeffrey; Wolff, Robert; Overman, Michael J.
Abstract : Lessons Learned : Panitumumab has no clinical activity in metastatic RAS wild‐type small bowel adenocarcinoma (SBA) and ampullary adenocarcinoma (AAC), possibly due to the foregut and midgut derivation of small bowel and ampulla. These results, along with findings from genomic characterization of SBA, suggest that SBA represents a unique intestinal malignancy and treatments should not be habitually extrapolated from colorectal cancer. Further studies evaluating the benefit of targeted therapies exclusively in SBA and AAC are warranted. Background: Given the benefit of epidermal growth factor receptor (EGFR) monoclonal antibodies in colorectal cancer (CRC), we sought to evaluate the efficacy of panitumumab in metastatic RAS wild‐type small bowel adenocarcinoma (SBA) and ampullary adenocarcinoma (AAC). Methods: We conducted a single‐center, open‐label, single‐arm, Bayesian phase II trial. The primary objective was response rate (RR). Panitumumab was administered at a dose of 6 mg/kg intravenously (IV) every 14 days. Results: Nine patients (male/female 7:2, median age: 61 years [range: 40–74], Eastern Cooperative Oncology Group [ECOG] performance status 0/1: 2/7) were enrolled from September 2013 to October 2015. One patient had AAC (pancreaticobiliary subtype) and eight patients had SBA (three duodenal, five jejunal/ileal). Acneiform rash was the most common toxicity. The study was stopped early due to futility with no responses, stable disease (SD) in two patients, and progression of disease (PD) in seven patients. Median progression‐free survival (PFS) and overall survival (OS) were 2.4 and 5.7 months, respectively. No patients had extended RAS mutations (exons 2/3/4), but two patients had BRAF G469A and one patient had PIK3CA H1074R mutations. Conclusion: Panitumumab had no clinically meaningful activity in patients with metastatic RAS wild‐type SBA and AAC. Our findings may relate to the primarily midgut and foregut derivation of the small bowel and ampulla.